Protecting Group-Free Synthesis of Glycopolymer-Type Amphiphilic Macromonomers and Their Use for the Preparation of Carbohydrate-Decorated Polymer Particles - Jin Motoyanagi (Biomolecules, 2019)
Polymer particles modified with carbohydrates on their surfaces are of significant interest, because their specific recognition abilities to biomolecules are valuable for developing promising materials in biomedical fields. Carbohydrate-decorated core-shell polymer particles are expected to be efficiently prepared by dispersion polymerization using a glycopolymer-based amphiphilic macromonomer as both a polymeric steric stabilizer and a monomer. To create glycopolymer-type macromonomers, we propose a new strategy combining living cationic polymerization of an alkynyl-functionalized vinyl ether (VE), and the click reaction for the preparation of glycopolymers having a polymerizable terminal group, and investigate their dispersion copolymerization with styrene for generating carbohydrate-decorated polymer particles. This study deals with (i) the synthesis of block copolymer-type amphiphilic macromonomers bearing a methacryloyl group at the α-terminus, and pendant alkynyl groups by living cationic polymerization of alkynyl-substituted VE (VEEP), (ii) the derivatization of maltose-carrying macromonomers by click chemistry of the pendant alkynyl groups of the precursor macromonomers with maltosyl azide without any protecting/deprotecting processes, and (iii) the preparation of maltose-decorated (Mal-decorated) polymer particles through the dispersion copolymerization of glycopolymer-type macromonomers with styrene in polar media. Moreover, this study concerns the specific interactions of the resultant polymer particles with the lectin concanavalin A (Con A).